The impact of supply chain management and the environmental performance - Cheay, Ying Wei (2022)
The objective of conducting this research is to investigate how supply chain management has an impact on the environmental performance in Malaysia freight forwarding industry. Thus, the independents variables have been selected in this research: logistics practices, supply chain practices, reversed logistics, and fleet management. Environmental performance is picked as the dependent variable. This research provides valuable insight and bring awareness to the freight forwarders to understand how these 4 independent variables have impacts on environmental performance. Institutional theory, legitimacy theory, and resourcebased view have been applied to study research. The data has been collected from 152 respondents who are from Selangor Freight Forwarder and Logistics Association (SFFLA) through survey questionnaire. All questionnaires are sent through e-mails, and the collected data has been analysed by Statistical Package of the Social Science (SPSS) software. The results are shown in table and figure forms in the research. Lastly, this research provides implication to the management, policy makers, and the government to make further improvement towards environmental performance in this industry. Limitations and recommendations have been addressed in this research to the future researchers in this study field.